Exploring the spectrum of variability and identifying donor genotypes fordrought stress tolerance in brinjal (Solanum melongena L.) - Prathibha, M D; Harsha, S G; Singh, T H; Shivashankara, K S; Laxman, R H (Journal of Horticultural Sciences, 2025)
Brinjal (Solanum melongena L.) is a nutritionally and commercially important crop and its productivity is hampered by drought stress. Screening and identification of stage specific donor genotypes possibly will be the strategy to improve the productivity. This study assessed the germination and seedling stage drought stress tolerance of 105 brinjal genotypes with polyethylene glycol (PEG). Two PEG concentrations viz., -2 and -6 bars along with water as control were used as treatments. The correlation and linear regression analysis indicated that total seedling length (TSL) and seedling vigor (SV) had highest correlation to drought stress. Stress tolerant genotypes namely Rayadurga Local, Arka Harshitha, Bethapudi local, Arka Avinash and IIHR-586 and Niranjan Bhata, had high and consistent individual and combined mean membership function value (MMFVC) signifying their higher moisture stress tolerance at seedling stage. Field evaluation of the contrasting genotypes showed that the genotypes with higher MMFVC had lower drought susceptibility index (DSI) indicating higher tolerance to drought stress. The findings from the field experiment are in line with the results of the laboratory study, indicating that genotypes with higher MMFVC values exhibit lower DSI values, and vice versa. This consistent pattern further strengthens the reliability of utilizing MMFVC as a preliminary screening method for identifying genotypes with promising stress tolerance capabilities
Keywords: Brinjal; germination; low moisture stress; membership function value; polyethylene glycol